Ajuste y predicción de la distribución Weibull a las estructuras diamétricas de plantaciones de pino de Durango, México - Maldonado Ayala, David; Návar Chaidez, José (Instituto de Ecología, A.C., 2016)
In this research the parameters of the Weibull distribution were estimated and predicted with stand attributes. Using hypothesis testing procedures, it was demonstrated that the equations to predict parameters, efficiently mimicked the diameter structures of forest stands used in the fitting as well as forest stands used in validating the prediction equations. Therefore, the equations are recommended to estimate the diameter structures of forest plantations of Durango, Mexico (Pinus durangensis, P. cooperi, P. engelmannii y P. arizonica).